The effectiveness of aspirin for migraine prophylaxis: a systematic review - Baena, Cristina Pellegrino; D’Amico, Raíssa Campos; Slongo, Helena; Brunoni, André Russowsky; Goulart, Alessandra Carvalho; Benseñor, Isabela (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Many researchers have suggested that aspirin prevents migraines. However, the evidence is unclear. The aim of this study was to analyze the available evidence on the effect of aspirinas a migraine prophylactic. DESIGN AND SETTING: Systematic review, conducted at the Pontifícia Universidade Católica do Paraná, Brazil, and at the University of São Paulo, Brazil. METHODS: We performed electronic searches in the databases of MEDLINE/PubMed, Ebase, WEB OF SCIENCE, the World Health Organization, CENTRAL and OpenGrey, and we also searched manually for interventional studies published before April 2016 that compared the effects of aspirin with a control, in adults. Two authors independently extracted data on the publication, population recruited, intervention (aspirin dosage, follow-up and combined treatment) and main outcomes (frequency, severity and dura- tion of migraine). We evaluated the quality of the studies using the Cochrane risk-of-bias tool. RESULTS: Our search retrieved 1,098 references, of which 8 met the selection criteria for this systematic review. The total population was 28,326 participants (18-64 years old); most (96%) were men. The dosage varied from 50 to 650 mg/day across the studies. The risk of bias was generally low or unclear. The only outcome for which most of the studies included (6/8) reported a significant reduction was frequency of migraine, which was reduced at an aspirin dosage of at least 325 mg/day. CONCLUSION: Aspirin can reduce the frequency of migraines. However, the optimal dosage is unclear.